Geoprocessamento como ferramenta de estudos hidrológicos e ambientais na mesorregião do Sudeste Paraense: Município de Marabá/PA - DANTAS FILHOS, Wandré Sady Araújo (2024)
The present work explains that geoprocessing is an important analysis tool for environmental studies. In the municipality of Marabá, east of the state of Pará, in the framework of Hydrographic Region the study area is in the Microregion of Tocantins-Araguaia (the second largest hydrographical network of the State of Pará), Mesoregion Baixo Tocantins and Microregion delimited by the Basin of Itacaiúnas. The present study is based on the integration of spatial data from sources such as the National Water Agency – ANA and the Brazilian Institute of Geography and Statistics – IBGE, providing a more comprehensive and integrated view of the characteristics of the hydrographic basin as to the relationship between its dynamics and its hydrological processes. The aim is to present the result of the geoprocessing applied to hydrological and environmental studies, considering interpolation and analysis of geospatial data, as well as the physiographic characterization of hydrographic basins (Rio Itacaiúnas and Rio Tapirapé). The study was carried out from a methodology containing research in a free database and through the cartographic confections and data compilation resulted in the characterization of the basins of Itacaiúnas and Tapirapé and their respective hydrographic networks. The results obtained and the information raised have been consistent with the results of previous works, where the information can serve as a basis for both basic environmental studies and more complex studies, subsidizing the manufacture of the same. Remote sensing and GIS tools facilitate the identification of possible environmental impacts, this data combination enables more accurate and cross-cutting decisions for the sustainable management of water resources.